Faktor Risiko Maternal Terhadap Kejadian Stunting Balita Usia 12 – 24 Bulan Di Puskesmas Mantangai Kabupaten Kapuas Provinsi Kalimantan Tengah - Titik Istiningsih; Riyanti Riyanti (Malahayati Nursing Journal, 2022)
ABSTRACTStunting is a condition when a child’s height is not in accordance with his/her age due to the lack of nutritional intake during pregnancy and early life. The incidence of stunting in Indonesia is high. Based on data from the Indonesian Toddler Nutrition Status Survey (SSGBI) in 2019, the percentage of stunted toddlers in Indonesia is 27.67% and still above the WHO target of 20%. “The risk needs to be aware because it will affect children’s growth directly both now or in the long term. Children who are in stunting condition will have neurodevelopmental disorders. This research aims to know the Maternal risk factors relatedto the incidence of stunting and the correlation between each variable (mother's height,body mass index, mothers’ occupational status and Antenatal Care (ANC) status) and the incidence of stunting for toddlers aged 12-24 months. This research used analytical observational method with cross sectional design. The total sample was 136 mothers who had toddlers aged 12-24 months in the area of Mantangai Public Health Center, Kapuas Regency, taken by consecutive sampling. The data was analyzed by univariate analysis, bivariate analysis with chi-square and multivariate analysis using multiple logistic regressiontest. The results showed the majority of respondents had normal height (75.7%), normalbody mass index (61.8%), mother’s status of jobless (82.4%), complete ANC status (87.5 %)The prevalence of stunting was 30.9%. The result of Chi Squared Status test of mothers’ occupational status with stunting incidence was p=0,007. Mother's height status with stuntingincidence was p = 0.224, maternal BMI status with stunting incidence was p = 0.719, andmaternal ANC status with stunting incidence was p = 0.207. Multivariate analysis showed mothers’ occupational status with stunting incidence was OR 0,285 (0,113-0,721) and p-value 0,008, then Antenatal Care status with stunting incidence was OR = 2,670 (1,093 – 6,526) and p-value 0,031. Mothers’ occupational status and ANC status have an influence on the incidence of stunting for toddlers aged 12-24 months at the Mantangai Public Health Center, Kapuas Regency, Central Kalimantan. Keywords: Risk, Maternal, Stunting, Toddler ABSTRAK Stunting merupakan kondisi  tinggi  badan seorang anak yang tidak  sesuai dengan  usianya  disebabkan  kekurangan  asupan gizi   pada   saat   dalam   kandungan   dan   awal kehidupan.  Angka kejadian stunting di Indonesia tergolong tinggi. Hasil Survei Status Gizi Balita Indonesia (SSGBI) tahun 2019 angka stunting di Indonesia yaitu 27,67 persen dan masih di atas angka yang ditargetkan WHO yaitu 20 persen. Risiko perlu diwaspadai karena akan mempengaruhi tumbuh kembang anak secara langsung baik sekarang maupun dalam jangka panjang. Anak yang mengalami stunting akan mengalami gangguan perkembangan otak. Tujuan penelitian ini ingin mengetahui faktor risiko Maternal yang berhubungan dengan kejadian stunting dan hubungan antara masing-masing variabel (Tinggi badan ibu, Indek Massa Tubuh, status pekerjaan dan status ANC)  terhadap kejadian stunting balita usia 12 – 24 bulan. Observasional analitik dengan design Cross sectional, dengan jumlah sampel 136 orang  ibu yang memiliki Balita usia 12-24 bulan di wilayah kerja puskesmas Mantangai kabupaten Kapuas, diambil secara consecutive sampling. Analisis data dengan analisis univariat, analisis bivariat dengan chi-square dan analisis multivariate menggunakan uji regresi logistic ganda. sebagian besar responden memiliki tinggi badan normal (75,7%), indeks masa tubuh (IMT) yang normal (61,8%), status pekerjaan tidak bekerja (82,4%), status ANC yang lengkap (87,5%). Prevalensi kejadian stunting sebesar 30,9%. Hasil uji chi Square Status Pekerjaan Ibu dengan kejadian stunting dengan nilai p=0,007. Status Tinggi Badan Ibu dengan kejadian stunting nilai  p=0,224, Status IMT Ibu dengan kejadian stunting (p=0,719), dan Status ANC Ibu dengan kejadian stunting (p=0,207).  Analisis multivariat menunjukkan Status Pekerjaan Ibu dengan kejadian stunting, ditunjukkan dengan nilai OR 0,285 (0,113-0,721) dan p-value 0,008 dan Status ANC Ibu dengan kejadian stunting dengan nilai OR = 2,670 (1,093 – 6,526) dan p-value 0,031. Kesimpulan: Status pekerjaan dan status ANC memiliki pengaruh terhadap kejadian stunting Balita Usia 12 – 24 Bulan di Puskesmas Mantangai Kabupaten Kapuas Provinsi Kalimantan Tengah. Kata Kunci: Risiko, Maternal, Stunting, Balita